Наукові та творчі здобутки В. Н. Станко - Котляр, Ю.В.; Ветушинська, Ю.В. (Історичний архів. Наукові студії, 2012)
Стаття містить матеріал про наукову спадщину видатного українського історика,
археолога, етнолога Володимира Никифоровича Станко. Висвітлено основні етапи
наукової діяльності вченого. Аналізуючи найвагоміші праці науковця, виділено коло
наукових інтересів В. Н. Станко. Стаття охоплює період життя історика з моменту
перших наукових спроб в університеті до фундаментальних праць у зрілому віці. Статья содержит материал о научном наследии выдающегося украинского
историка, археолога, этнолога Владимира Никифоровича Станко. Освещени основные
этапы научной деятельности ученого. Анализируя значимые работы ученого,
выделено круг научных интересов В. Н. Станко. Статья охватывает период жизни
историка с момента первых научных попыток в университете до фундаментальных
трудов в зрелом возрасте. This article contains material on the scientific heritage of the famous Ukrainian historian,
archaeologist, ethnologist Vladimir Stanko. The author aims to highlight the main stages of
scientific activity of scientist. Analyzing the basic most significant work of the scientist, the
author was selected circle of scientific interests of Stanko. The article covers the period of
historian’s living since the first scientific attempts at the University to the fundamental works in
adulthood.